Molded catalyst body
By developing chromium-free copper catalyst molded bodies, the problem of environmental pollution in existing copper-chromium catalysts is solved, and more efficient catalytic performance is achieved at lower pressures and temperatures, reducing operating costs and extending catalyst life.
Patent Information
- Application Number
- CN202380048202.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-22
- Filing Date
- 2023-06-21
- Publication Date
- 2025-03-04
AI Technical Summary
The copper-chromium catalyst used in the hydrogenolysis reaction of carboxylic acid ester in the prior art has environmental pollution problems and operates under higher pressures, resulting in increased difficulty in equipment design and control and higher cost.
A chromium-free copper catalyst molded body was developed, prepared by precipitation and heat treatment methods, with low bulk density and specific pore volume distribution, suitable for hydrogenation, dehydrogenation, hydrogenolysis or acetyleneization reactions at lower pressures and temperatures.
Improved catalytic performance for hydrogenation, dehydrogenation, hydrogenolysis or acetyleneization reactions at lower pressures and temperatures is achieved, reducing equipment operating costs and extending the operating life of the catalyst.
Smart Images

Figure CN119562859A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to shaped catalyst bodies containing copper, aluminum and manganese, a process for producing the shaped catalyst bodies, and a process for hydrogenation, dehydrogenation, hydrogenolysis or ethynylation using the shaped catalyst bodies. Background Art
[0002] In recent years, due to the health requirements of the fight against the coronavirus pandemic, the fatty alcohol produced by the hydrogenolysis of carboxylic acid esters has shown a significant increase in demand. Heterogeneous catalysts (including precious metals, nickel, cobalt and copper) are widely used in this reaction. Commercial catalysts for the hydrogenolysis of fatty acid esters generally utilize copper-chromium (Cu-Cr) composite materials with high performance and mechanical stability. However, it is expected that the environmental problems related to the disposal of chromium-containing catalysts will eventually eliminate their use in many countries. Therefore, it is more advantageous and sustainable to replace the Cu-Cr catalyst currently used in the hydrogenolysis of carboxylic acid esters with a Cu-containing catalyst that does not contain Cr with good catalyst activity. The material containing CuZn, CuMn or CuMnAl in the shape of pellets and extrudates can be used as an active catalyst for the hydrogenolysis of carboxylic acid esters.
[0003] U.S. Patent No. 10226760B2 describes a tableted Cu-Zn catalyst starting from a heat-treated metal carbonate mixture produced by a precipitation process. It has been found that the carbonate content is correlated with the Cu metal surface area of the reduced catalyst. In the example, the catalyst was used to hydrogenolyze a C12 methyl ester feed at a temperature of 180°C and a pressure of 280 bar. The catalyst they invented showed a significant increase in the conversion of C12 methyl ester compared to a comparative catalyst produced with a lower carbonate content.
[0004] US Patent No. 10315188B2 discloses a CuMnAl pelletized catalyst body obtained by adding a graphite material having a specific particle size of 5.0 μm ≤ D90 ≤ 17.5 μm. In an example, the catalyst they invented is used to hydrogenate a C12 methyl ester feed at a temperature of 180°C and a pressure of 280 bar. It has been found that adding graphite with a smaller particle size and a larger surface area can increase the conversion of esters and reduce the selectivity of paraffin by-products.
[0005] U.S. Patent No. 10434500B2 describes a catalyst body of CuAl tablets, which is obtained by a mixture of calcined and uncalcined carbonates produced by a precipitation method. The catalyst they invented has a special bimodal porosity, in which pores with pore diameters in the range of 500 to 2500nm account for about 13% of the pore volume, and pores with pore diameters in the range of 5 to 45nm account for about 75% of the pore volume. However, the pore volume formed by pores with pore diameters in the range of 45 to 200nm is less than 10%. It has been found that the pore volume of the catalyst after tableting, calcination and reduction varies with the change of the uncalcined carbonate content. In the activity measurement example, the catalyst they invented was measured at 160°C, 180°C and 240°C at a pressure of 280 bar for the hydrogenolysis of C12-methyl ester feed. It has been observed that at all three selected temperatures, the catalyst with a higher pore volume caused by uncalcined carbonate can lead to a higher conversion rate of fatty acid esters than the comparative catalyst.
[0006] In addition to the prior art of the chromium-free copper catalyst tablets for hydrogenolysis of fatty acid esters above, a catalyst in the shape of an extrudate for this application is also disclosed. Generally, compared with catalyst tablets, catalyst extrudates have significantly higher pore volume and lower bulk density while at least maintaining comparable mechanical strength. U.S. Patent No. 10639616B2 describes a catalyst extrusion object, which comprises 20-43wt% Cu, 20-40wt% Al and 1-10wt% Mn based on the total weight of the catalyst, wherein more than 50% of the pore volume is formed by holes with an aperture in the range of 7 to 40nm. However, the pore volume formed by holes with an aperture in the range of 45 to 200nm is less than 10%. It has been observed that the extrudate catalyst they invented has a higher pore volume and a lower bulk density than the comparative catalyst in the form of tablets. The catalyst they invented hydrogenates C12 methyl ester feed at a pressure of 280 bar at a temperature of 160°C, 180°C and 240°C. The data shows that the productivity of the target products has been significantly improved.
[0007] In the commercial use of catalysts in methyl ester hydrogenolysis, as disclosed in the above-mentioned prior art, it is carried out in a liquid phase process, which is typically operated at a higher pressure range to promote ester conversion and alcohol selectivity. This leads to higher requirements for reactor design and control difficulty and higher costs. If the reaction can be carried out at lower pressures and achieve similar productivity, this will result in considerable cost savings and lower risks for equipment operation. In addition, the pressure reduction will be beneficial to extend the operating life of the catalyst, especially when the catalyst is not stable enough in terms of mechanical strength.
[0008] Against this background, it was an object of the present invention to provide a chromium-free copper catalyst which has improved catalytic properties for hydrogenation, dehydrogenation, hydrogenolysis or ethynylation at lower pressures and temperatures. Summary of the invention
[0009] It has been found, surprisingly, that this object is achieved by shaped catalyst bodies which, compared with conventional shaped catalysts, have a significantly lower bulk density and a pore volume within a specific range.
[0010] Thus, in one aspect, the present invention is directed to a shaped catalyst body comprising copper, aluminum, and manganese, wherein the shaped catalyst body has a bulk density of 0.87 to 1.43 g / cc.
[0011] In another aspect, the present invention relates to a method for producing the shaped catalyst body, the method comprising:
[0012] a) precipitating by combining an aqueous solution of a copper compound, a manganese compound, an aluminum compound and a precipitant;
[0013] b) filtering the slurry and washing the precipitate;
[0014] c) drying and calcining at a temperature in the range of 200° C. to 1000° C. to form a heat-treated intermediate;
[0015] d) mixing the heat-treated intermediate; and
[0016] e) forming into a shaped body.
[0017] In a further aspect, the invention relates to a process for hydrogenation, dehydrogenation, hydrogenolysis, or ethynylation using a shaped catalyst body. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The pore size distribution of Example 1 is shown.
[0019] Figure 2 The pore size distribution of Example 2 is shown.
[0020] Figure 3 The pore size distribution of Example 3 is shown.
[0021] Figure 4 The pore size distribution of Comparative Example 1 is shown.
[0022] Figure 5 The pore size distribution of Comparative Example 2 is shown. DETAILED DESCRIPTION
[0023] Before describing several exemplary embodiments of the present invention, it should be understood that the present invention is not limited to the details of construction or process steps set forth in the following description. The present invention may have other embodiments and may be implemented or carried out in various ways.
[0024] With respect to terms used in this disclosure, the following definitions are provided.
[0025] Throughout the specification, including the claims, the terms "comprise", "comprising", and the like are used interchangeably with "contain", "containing", and the like and are to be interpreted in a non-limiting, open manner. That is, for example, additional components or elements may be present. The expression "consisting of" or "consisting essentially of" or cognates may be included in "comprise" or cognates.
[0026] As used herein, "about" will be understood by one of ordinary skill in the art and will vary to some extent depending on the context in which the term is used. If the use of the term is not clear to one of ordinary skill in the art, then in the context in which the term is used, "about" will mean up to plus or minus 10% of the particular term.
[0027] The terms "a," "an," and "the" are used to refer to one or to more than one (ie, to at least one) of the grammatical object of the article.
[0028] The term "and / or" includes the meanings "and", "or" and also all other possible combinations of the elements related to this term.
[0029] According to a first aspect, the present invention provides a shaped catalyst body containing copper, aluminum and manganese, wherein the shaped catalyst body has a bulk density of 0.87 to 1.43 g / cc, preferably 0.90 to 1.42 g / cc, more preferably 0.95 to 1.35 g / cc. For example, the bulk density includes, but is not limited to, about 0.87 g / cc, about 0.90 g / cc, about 0.93 g / cc, about 0.95 g / cc, about 1.0 g / cc, about 1.10 g / cc, about 1.20 g / cc, about 1.30 g / cc, about 1.35 g / cc, about 1.40 g / cc, about 1.42 g / cc, about 1.43 g / cc, or any range including and / or between any two of the foregoing values.
[0030] All references to bulk density in the present specification and claims are based on measurements made using the method described in ASTM-D4164-03.
[0031] In some embodiments according to the present invention, the shaped catalyst body comprises 30% to 75%, preferably 40% to 65%, more preferably 45% to 60% by weight of Cu calculated as CuO. For example, the amount of copper oxide may include, but is not limited to, about 30wt%, 35wt%, about 40wt%, about 45wt%, about 50wt%, about 55wt%, about 60wt%, about 65wt%, about 70wt%, about 75wt%, or any range including and / or between any two of the foregoing values.
[0032] It is to be understood that the copper oxide and at least one oxide of the other metal (or element), when present, may be present as individual oxides, or as a composite oxide of copper and the other metal (or element), or a combination thereof.
[0033] In some embodiments according to the present invention, the shaped catalyst body comprises 10% to 50%, preferably 20% to 40%, more preferably 25% to 35% by weight of Al calculated as Al2O3. For example, alumina can be present in an amount of about 10 wt%, 15 wt%, about 20 wt%, about 25 wt%, about 30 wt%, about 35 wt%, about 40 wt%, about 45 wt%, about 50 wt%, or in any range including and / or between any two of the foregoing values.
[0034] It is to be understood that aluminum oxide and at least one oxide of other metal (or element), when present, may be present as individual oxides, or composite oxides of aluminum and other metal (or element), or combinations thereof.
[0035] In some embodiments according to the present invention, the shaped catalyst body comprises 1% to 25%, preferably 5% to 20%, more preferably 7% to 15% by weight of Mn calculated as MnO2. For example, manganese oxide can be present in an amount of about 1 wt%, about 2 wt%, about 3 wt%, about 4 wt%, about 5 wt%, about 6 wt%, about 7 wt%, about 8 wt%, about 9 wt%, about 10 wt%, about 11 wt%, about 12 wt%, about 13 wt%, about 14 wt%, about 15 wt%, about 16 wt%, about 17 wt%, about 18 wt%, about 19 wt%, about 20 wt%, about 21 wt%, about 22 wt%, about 23 wt%, about 24 wt%, about 25 wt%, or in an amount including and / or in any range between any two of the foregoing values.
[0036] It is to be understood that the manganese oxide and at least one oxide of the other metal (or element), when present, may be present as individual oxides, or as a composite oxide of manganese and the other metal (or element), or a combination thereof.
[0037] In some embodiments according to the present invention, the shaped catalyst body may include a binder, wherein the binder includes but is not limited to calcium silicate, sodium silicate, silica sol, clay, boehmite, and mixtures thereof.
[0038] In some embodiments according to the present invention, the binder includes a zirconium component. In any embodiment herein, the zirconium component may exist in the form of a reduced metal or oxide, or exist as a precursor of such a form, and exist in one or more oxidation states as described above. For example, the zirconium component exists in the form of zirconium oxide. In any embodiment herein, the zirconium component exists in the amount of Zr calculated as ZrO2 of about 3wt% to about 20wt% by weight. Suitable amounts of the zirconium component include, but are not limited to, about 5wt% to about 15wt%, about 5wt% to about 12wt%, about 5wt% to about 8wt%, or any range including and / or between any two of the aforementioned values. For example, the zirconium component can be present in an amount of about 3 wt%, about 4 wt%, about 5 wt%, about 6 wt%, about 7 wt%, about 8 wt%, about 9 wt%, about 10 wt%, about 11 wt%, about 12 wt%, about 13 wt%, about 14 wt%, about 15 wt%, about 16 wt%, about 17 wt%, about 18 wt%, about 19 wt%, about 20 wt%, or in any range including and / or between any two of the foregoing values.
[0039] In any embodiment, the shaped catalyst body as described herein may further include an alkali metal component. In any embodiment of the present invention, the alkali metal is selected from the group consisting of sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), and combinations thereof. These metals may exist in the form of reduced metals or oxides, or as precursors of such forms, and exist in one or more oxidation states as described above. For example, the alkali metal component may include sodium in the form of disodium oxide. In any embodiment of the present invention, the alkali metal may be present in an amount of about 0wt% to about 1wt% by weight of the shaped catalyst body. For example, the alkali metal component may be present in an amount of about 0.01wt%, 0.05wt%, about 0.1wt%, about 0.2wt%, about 0.3wt%, about 0.4wt%, about 0.5wt%, about 0.6wt%, about 0.7wt%, about 0.8wt%, about 0.9wt%, about 1wt%, or in an amount including and / or between any two of the aforementioned values.
[0040] In some embodiments according to the present invention, the shaped catalyst body has a bimodal pore size distribution.
[0041] All references to pore diameter and pore volume in the present specification and claims are based on measurements made using mercury intrusion porosimetry as described in ASTM-D4284-03.
[0042] In a specific embodiment according to the present invention, the shaped catalyst body exhibits a pore volume of 0.02 to 0.50 ml / g, preferably 0.15 to 0.30, having a pore diameter in the range of 45 to 200 nm, for example, the pore volume includes but is not limited to about 0.02 ml / g, about 0.05 ml / g, about 0.10 ml / g, about 0.15 ml / g, about 0.18 ml / g, about 0.20 ml / g, about 0.22 ml / g, about 0.25 ml / l / g, about 0.27 ml / g, about 0.30 ml / g, or any range including and / or between any two of the aforementioned values; and a pore volume of 0.20 to 0.60 ml / g, preferably 0.25 to 0.50, having a pore diameter in the range of 10 to 200 nm. For example, the pore volume includes, but is not limited to, about 0.20 ml / g, about 0.25 ml / g, about 0.30 ml / g, about 0.35 ml / l / g, about 0.40 ml / g, about 0.45 ml / l / g, about 0.50 ml / g, about 0.55 ml / g, about 0.60 ml / g, or any range including and / or between any two of the foregoing values.
[0043] In other specific embodiments according to the present invention, 10% to 80%, preferably 35% to 70%, more preferably 45% to 65% of the pore volume of the shaped catalyst body is formed by pores having a pore size in the range of 45 to 200 nm. For example, the percentage includes, but is not limited to, about 10%, about 15%, about 20% ml / g, about 25%, about 30%, about 35%, about 40%, about 45%, about 50%, about 55%, about 60%, about 65%, about 70%, about 75%, about 80%, or any range including and / or between any two of the aforementioned values; and 70% to 100% of the pore volume is formed by pores having a pore size in the range of 10 to 200 nm. For example, the percentage includes, but is not limited to, about 70%, about 75%, about 80%, about 85%, about 90%, about 95%, about 100%, or any range including and / or between any two of the aforementioned values.
[0044] In some embodiments according to the present invention, the shaped catalyst body catalyst may have a size of about 15 m 2 / g to about 70m 2 For example, the calcined shaped catalyst body has a BET surface area of about 15 m2 / g, about 20 m2 / g, and about 10 m2 / g. 2 / g, about 25m2 / g, about 30m 2 / g, about 35m2 / g, about 40m 2 / g, about 45m 2 / g, about 50m 2 / g, about 55m2 / g, about 60m 2 / g, about 65m 2 / g, about 70m 2 / g, or a BET surface area having any range including and / or between any two of the foregoing values. In any embodiments herein, the calcined hydrogenation catalyst has a BET surface area of about 15 m 2 / g to about 70m 2 / g, about 25m 2 / g to about 65m 2 / g, about 45m 2 / g to about 60m 2 / g, about 50m 2 / g to about 60m 2 / g, or any range of BET surface areas including and / or between any two of the foregoing values.
[0045] According to a second aspect, the present invention provides a method for producing a shaped catalyst body, the method comprising:
[0046] a) precipitating by combining an aqueous solution of a copper compound, a manganese compound, an aluminum compound and a precipitant;
[0047] b) filtering the slurry and washing the precipitate;
[0048] c) drying and calcining at a temperature in the range of 200° C. to 1000° C. to form a heat-treated intermediate;
[0049] d) mixing the heat-treated intermediate; and
[0050] e) forming into a shaped body.
[0051] The shaped catalyst bodies can be provided as tablets or extrudates. One way to process the blend of all ingredients is to extrude it through a forming hole to form an extruded catalyst body, or extrudate. Other catalyst bodies can be formed into spheres or any other convenient form. Another way is to tablet the catalyst. The shaped catalyst has a size of 1 / 32" to 8 mm. For example, the hydrogenolysis catalyst can be extruded or tableted into sizes including, but not limited to, 1 / 8"×1 / 8", 3 / 16"×3 / 16", 1 / 4"×1 / 4", 3 / 16"×1 / 4", 1 / 4"×1 / 16" or 1 / 8"×1 / 16".
[0052] In some embodiments according to the present invention, the shaped catalyst body may be calcined. In any embodiment herein, the catalyst is a calcined and tableted catalyst.
[0053] The method includes calcining the material mixture at a temperature sufficient to solidify the calcined hydrogenolysis catalyst and continuing the time sufficient to solidify the calcined hydrogenolysis catalyst. In any embodiment herein, the calcination can occur at a temperature of about 200°C to about 1000°C. For example, the calcination can occur at a temperature of about 200°C, about 250°C, about 300°C, about 350°C, about 400°C, about 450°C, about 500°C, about 550°C, about 600°C, about 650°C, about 700°C, about 750°C, about 800°C, about 850°C, about 900°C, about 950°C, about 1000°C, or at a temperature including and / or between any two of the aforementioned values. In any embodiment herein, the calcination temperature can be about 300°C to about 800°C, about 400°C to about 750°C, or about 500°C to about 700°C. In any embodiments herein, the calcination can occur over a period of about 0.5 h to about 4 h. In any embodiments, the calcination can occur over a period of about 0.5 h, about 1 h, about 1.5 h, about 2 h, about 2.5 h, about 3 h, about 3.5 h, about 4 h, or over a period of time including and / or between any two of the foregoing values.
[0054] According to a further aspect, the present invention provides a process for hydrogenation, dehydrogenation, hydrogenolysis or ethynylation using the shaped catalyst bodies according to the invention.
[0055] The shaped catalyst bodies of the present invention are suitable for use in a number of hydrogenation reactions. Preferably, the shaped catalysts of the present invention are suitable for the liquid phase hydrogenolysis of a mixture of carboxylic acids and esters, preferably fatty acid methyl esters having 5 to 24 carbon atoms, to form the corresponding fatty alcohols. In particular, the hydrogenolysis reaction of fatty acid methyl esters is suitable for operation at a specific pressure in the range of 60 to 250 bar, more preferably in the range of 75 to 100 bar.
[0056] Various embodiments are described below. It should be noted that the specific embodiments are not intended as an exhaustive description or limitation of the broader aspects discussed herein.
[0057] Examples
[0058] Example 1
[0059] 122.2 g of Cu(NO3)2 (15.5 wt% Cu) solution was weighed out and mixed with Mn(NO3)2 solution (wherein the molar ratio of Cu / Mn was 5.2 / 1.0). NaAlO2 (12.5 wt% Al) solution (wherein the molar ratio of Cu / Al was 1.2 / 1.0) was weighed out and diluted with 18.9 g of deionized H2O. 450 ml of deionized H2O was added to a container. 90.7 g of Na2CO3 powder was weighed out and dissolved in deionized H2O to 500 ml. Cu(NO3)2, Mn(NO3)2, NaAlO2 and Na2CO3 solutions were added to 450 ml of deionized H2O simultaneously. The slurry was kept at a constant neutral pH during the precipitation process. The precipitation temperature was kept constant at room temperature. Afterwards, the precipitate was filtered, washed, and dried. The dried material was calcined in air at 600°C to obtain a calcined metal carbonate material.
[0060] The above calcined metal carbonate powder was mixed with graphite powder. After that, the mixture was formed into particles via a briquetting step, and the particles were then tableted to form a molded body. The tablets were then calcined at 750°C. The material had a bulk density of 1.4 g / ml, a pore volume of 0.26 ml / g and a pore volume of 53 m 2 93% of the pore volume is formed by pores having a pore diameter in the range of 10 to 200 nm, and specifically, 30% of the pore volume is formed by pores having a pore diameter in the range of 45 to 200 nm.
[0061] Example 2
[0062] The calcined metal carbonate powder material in Example 1 was mixed with graphite powder. The mixture was then formed into particles having a specific bulk density, which was 40% to 50% of the value of the corresponding tablet product, by a briquetting step. The specific particles were then tableted to form a shaped body. The tablets were then calcined at 750°C. The material had a bulk density of 1.1 g / ml, a pore volume of 0.41 ml / g and a pore volume of 50 m 2 93% of the pore volume is formed by pores having a pore diameter in the range of 10 to 200 nm, and specifically, 59% of the pore volume is formed by pores having a pore diameter in the range of 45 to 200 nm.
[0063] Example 3
[0064] The calcined metal carbonate powder material in Example 1 was mixed with zirconium acetate, aluminum oxide, an organic binder, water, and then kneaded to form a wet mixture having a composition of 52 wt% CuO, 10 wt% MnO2, 30 wt% Al2O3, and 8 wt% ZrO2. The mixture was then extruded with an extruder to form a molded body. The extrudate was then calcined at 500°C. The material had a bulk density of 1.0 g / ml, a pore volume of 0.31 ml / g, and a pore volume of 50 m 2 76% of the pore volume is formed by pores having a pore diameter in the range of 10 to 200 nm, and specifically, 21% of the pore volume is formed by pores having a pore diameter in the range of 45 to 200 nm.
[0065] Comparative Example 1
[0066] The metal carbonate powder material was produced by the method described in Example 1. Thereafter, the carbonate material was calcined at 800° C. in air and then mixed with calcium hydroxide, attapulgite, a plasticizer, silica gel, water and then kneaded to form a wet mixture having a composition of 40 wt % CuO, 10 wt % MnO2, 20 wt % A12O3, 20 wt % SiO2 and 10 wt % CaO. The mixture was then extruded with an extruder to form a molded body. The extrudate was then calcined at 500° C. It had a bulk density of 0.8 g / m1, a pore volume of 0.38 ml / g and a pore volume of 45 m 2 / g of BET surface area.
[0067] Comparative Example 2
[0068] 500 g of CuO powder was mixed with calcium hydroxide, plasticizer, silica gel, hydroxypropyl methylcellulose, water and then kneaded to form a wet mixture having a composition of 58 wt% CuO, 21 wt% SiO2 and 14 wt% CaO. The mixture was then extruded with an extruder to form a molded body. The extrudate was then calcined at 500° C. The material had a bulk density of 0.8 g / ml and a particle size of 50 m 2 / g of BET surface area.
[0069] Comparative Example 3
[0070] 591 g of Cu(NO3)2 (15.5 wt% Cu) solution was weighed out and mixed with Al(NO3)3 solution (4.2 wt% Al) (wherein the molar ratio of Al / Cu was 1.56 / 1.0) and 170 g of deionized H2O. 442 g of Na2CO3 powder was weighed out and dissolved with 1770 g of deionized H2O. Cu(NO3)2, Al(NO3)3 and Na2CO3 solutions were added to separate containers simultaneously. The slurry was maintained at a constant pH of about 6.0 during the precipitation process. The precipitation temperature was kept constant at 80°C. Thereafter, the precipitate was aged, filtered, washed, and dried. 507 g of the dry powder, 87 g of pseudo-boehmite, 21 ml of formic acid and 375 g of water were mixed and kneaded to form a wet mixture. The mixture was then extruded to form an extrudate material, which was subsequently calcined at 600°C. The material had a bulk density of 0.85 g / ml and a carbonyl content of 21 m 2 / g of BET surface area.
[0071] Comparative Example 4
[0072] 320 g of Zn(NO3)2*6H2O and 336.4 g of Al(NO3)3*9H2O were weighed out and dissolved in 600 ml of deionized water. 300 g of Na2CO3 powder was weighed out and dissolved with 1200 g of deionized water. Both solutions were added simultaneously to a separate container with a controlled neutral pH at a temperature of 50°C. Afterwards, the precipitate was aged, filtered, washed, dried and calcined at 400°C.
[0073] The above calcined powder was partially redissolved in a mixed solution of HNO3, Cu(NO3)2 and Zn(NO3)2 (atomic ratio of Cu:Zn = 65:13) to form a suspension having a total atomic ratio of Cu:Zn:Al = 65:25:10. This suspension and a 20 wt% Na2CO3 solution were simultaneously added to a separate container having a controlled pH of 6.8 at a temperature of 70°C. Thereafter, the precipitate was aged, filtered, washed, dried and calcined at 300°C.
[0074] Tablets are produced from the powder after mixing with graphite powder, crushing and granulation. These granules are then pressed into tableted catalyst bodies. The material described has a bulk density of 1.45 g / ml and a pore volume of 0.20 ml / g.
[0075]
[0076] Hydrogenolysis of fatty acid methyl esters (FAME)
[0077] The activity of the catalyst was tested in a multichannel fixed bed reactor as follows. Each catalyst bed was formed in an electric heating tubular reactor by 2.5 ml catalyst tablets or extrudates, which were supplied with hydrogen and nitrogen feeds and a device for feeding C12-C18 methyl ester raw material liquid to the top of the catalyst bed. The catalyst was first activated by a method known in the industry. When the activation procedure was complete, the temperature and pressure were then adjusted to the desired reaction temperature and pressure and allowed to balance under hydrogen. The reaction was started by starting the feed of methyl esters and hydrogen. Product samples were taken out after the reaction and allowed to balance under each set of reaction conditions for 8 hours. Samples of raw materials and products were analyzed by gas chromatography to assess the conversion of esters and the selectivity to hydrocarbon by-products.
[0078] Temperature range: 170°C to 250°C
[0079] Pressure range: 75 to 250 bar
[0080] LHSV range: 0.3 to 1.5h -1
[0081] H2 / raw material molar ratio: (50-100) / 1
[0082] Tables 2 and 3 show the values of ester conversion and selectivity to hydrocarbons obtained under different temperature and pressure conditions.
[0083] The shaped catalyst with low bulk density, higher pore volume and specific pore size distribution produced according to the present invention has higher methyl ester conversion and similar selectivity to hydrocarbon by-products than the comparative example. This conversion difference is more significant at the selected moderate reaction pressure of 75 bar, 100 bar and the selected moderate temperature of 170° C., 190° C. Therefore, it can be said that the operation of the equipment with the catalyst of the present invention will lead to considerable cost savings and lower risks due to the mild operating temperature and pressure range.
[0084] Table 2 Ester conversion rates of examples and comparative examples
[0085]
[0086]
[0087] Table 3 Selectivity of Examples and Comparative Examples to Hydrocarbons
[0088]
[0089] Therefore, it can be said that the catalyst of the present invention fully converts ester into the target product under mild reaction conditions such as moderate pressure and temperature during equipment operation, which means considerable cost savings and lower risks.
Claims
1. A shaped catalyst body comprising copper, aluminum and manganese, wherein the shaped catalyst body has a bulk density of 0.87 to 1.43 g / cc.
2. The shaped catalyst body according to claim 1, wherein The shaped catalyst bodies comprise 30 to 75% by weight of Cu, calculated as CuO.
3. The shaped catalyst body according to claim 1 or 2, wherein The shaped catalyst body comprises 10 to 50% by weight of Al, calculated as Al2O3.
4. The shaped catalyst body according to claim 1, wherein: The shaped catalyst bodies comprise 1 to 25% by weight of Mn, calculated as MnO2.
5. The shaped catalyst body according to claims 1 to 4, wherein The shaped catalyst bodies have a bulk density of from 0.90 to 1.42 g / cc, preferably from 0.95 to 1.35 g / cc.
6. The shaped catalyst body according to claims 1 to 5, wherein The shaped catalyst bodies have a pore volume of 0.1 to 0.5 ml / g, preferably 0.2 to 0.4 ml / g.
7. The shaped catalyst body according to claims 1 to 6, wherein The shaped catalyst bodies comprise 40 to 65% by weight, preferably 45 to 60% by weight, of Cu, calculated as CuO.
8. The shaped catalyst body according to claims 1 to 7, wherein The shaped catalyst bodies comprise 20 to 40% by weight, preferably 25 to 35% by weight, of Al, calculated as Al2O3.
9. The shaped catalyst body according to claims 1 to 8, wherein The shaped catalyst bodies comprise 5 to 20% by weight, preferably 7 to 15% by weight, of Mn, calculated as MnO2.
10. The shaped catalyst body according to claims 1 to 9, wherein The shaped catalyst body further comprises 3 to 20% by weight, preferably 5 to 15% by weight, of Zr, calculated as ZrO2.
11. The shaped catalyst body according to claims 1 to 10, wherein The shaped catalyst bodies have a bimodal pore size distribution.
12. The shaped catalyst body according to claim 11, wherein The shaped catalyst bodies exhibit a pore volume of 0.02 to 0.50 ml / g, preferably 0.15 to 0.30 ml / g, of pores having a pore diameter in the range from 45 to 200 nm and a pore volume of 0.20 to 0.60 ml / g, preferably 0.25 to 0.50 ml / g, of pores having a pore diameter in the range from 10 to 200 nm.
13. The shaped catalyst body according to claim 11 or 12, wherein 10% to 80% of the pore volume is formed by pores having a pore size in the range of 45 to 200 nm, and 70% to 100% of the pore volume is formed by pores having a pore size in the range of 10 to 200 nm.
14. The shaped catalyst body according to claim 13, wherein 35% to 70%, preferably 45% to 65%, of this pore volume is formed by pores having a pore diameter in the range from 45 to 200 nm.
15. A method for producing a shaped catalyst body according to any one of claims 1 to 14, the method comprising: a) precipitating by combining an aqueous solution of a copper compound, a manganese compound, an aluminum compound and a precipitant; b) filtering the slurry and washing the precipitate; c) drying and calcining at a temperature in the range of 200° C. to 1000° C. to form a heat-treated intermediate; d) mixing the heat-treated intermediate; as well as e) forming into a shaped body.
16. A process for hydrogenation, dehydrogenation, hydrogenolysis or ethynylation using the shaped catalyst body according to any one of claims 1 to 14.
Citation Information
Patent Citations
Hydrogenation catalyst and method for producing same
US10226760B2
Catalyst molded body containing graphite
US10315188B2
Hydrogenation catalyst and process for production thereof by the use of uncalcined starting material
US10434500B2
Extruded Cu—Al—Mn hydrogenation catalyst
US10639616B2